The INFLUENCE OF GREEN MARKETING ON GREEN PURCHASE INTENTION MEDIATED BY ENVIRONMENTAL AWARENESS - Risyafani, Sonia; Musnaini, Musnaini; Adriani, Zulfina (Management Department, Faculty of Economics and Business, Universitas Jambi, 2024)
This study aims to explain how Green Marketing influences Green Purchase Intention mediated by Environmental Awareness among Starbucks consumers in Jambi City. The sampling method used is Purposive Sampling with a total of 100 respondents. Primary data were obtained through a questionnaire using a Likert scale. The data analysis method employed Partial Least Square (PLS) with Smart PLS 4.0 software. The results showed that Green Marketing has a positive and significant effect on Environmental Awareness, and Environmental Awareness has a positive and significant effect on Green Purchase Intention. Green Marketing also has a positive and significant impact on Green Purchase Intention mediated by Environmental Awareness. Based on these findings, it is suggested that marketers implement Green Marketing strategies strengthened by enhancing consumer Environmental Awareness, as consumer attitudes and concerns about the environment can increase the intention to purchase environmentally friendly products. Keyword: Green Marketing, Environmental Awarenss, Green Purchase Intention